SYNCHRONIZATION OF ESTRUS WITH GnRH AND PGF2alpha DURING EARLY POSTPARTUM IN MEHSANA BUFFALOE - AWASTHl, M K; KAVANI, F S; DHAMI, A J; PANCHAL, M T (The Indian Journal of Animal Reproduction, 2023)
Present experiment was conducted to assess efficacy of estrus synchronization protocol using combination of GnRH and PGF2alpha administration in postpartum Mehsana buffaloes (n=12) beginning on day 35 postpartum (day O for proposed protocol) with 20 μg Buserelin acetate i/m, followed by i/m injection of 25 mg Dinoprost tromethamin 10 days later. Another 6 animals of similar reproductive status were kept as control. Estrus was detected in animals twice daily and estrus animals were served with known fertile buffalo bull. Three animals showed premature estrus between days O and 10, i.e. prior to injection of prostaglandin, while 4 animals (33.33%) exhibited synchconized estrus after PGF2alpha treatment. One animal with premature estrus and three animals with synchronized estrus conceived after service at induced estrus giving overall conception rate of 57.14% (4,7), whereas overall pregnancy rate was 33.33% (4/12). When the subsequent reproductive performance was compared between animals of treatment and control groups non-significant difference was recorded in occurrence of first postpartum estrus (74.5 ± 10.24 vs. 59.33 ± 7.92 days), calving to conception interval (95.0 ± 12.10vs. 77.0 ± 20.36 days) and number of services per conception ( 1.50 ± 0.24 vs. 1.50 ± 0.37). From the present study, it is concluded that estrus synchronization protocol using combination of GnRH and PGF2alpha administration may induce fertile estrus, however, there was no beneficial effect on subsequent reproductive performance of treated animals.